Negotiating Gender, Policy and Politics in the Caribbean : Feminist Strategies, Masculinist Resistance and Transformational Possibilities. - Hosein, Gabrielle (Rowman & Littlefield International, 2017)
Drawing on rich empirical research, this book examines the evolution and success of feminist strategies to promote democratic governance, women's rights and gender equality in the Caribbean.